Dynamics of Philosophical Interpretation of the Classical Period: A Historical Approach - Niila Khoiru Amaliya (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2025)
This study aims to study the dynamics of philosophical interpretation within the Qur'anic exegesis, specifically during the classical period, by portraying the figures of Al-Farabi, Al-Ghazali, and Ibn Rushd. These three figures were chosen because they significantly influenced their respective eras. This was done as an effort to systematically observe the journey of philosophical interpretation by examining its dynamics in a more coherent manner, thus avoiding confusion. This research is a form of qualitative, descriptive library research. The approach used is a historical approach, depicting Al-Farabi, Al-Ghazali, and Ibn Rushd sequentially based on their respective lifetimes. The resulting data were analyzed using a historical analysis approach and found that philosophical interpretation, or interpretation with a philosophical character, experienced fluctuating responses. Sometimes it was accepted and sometimes it was rejected. In the hands of Al-Farobi, philosophical interpretation was studied and developed. However, during Al-Ghazali's time, philosophical interpretation was rejected. With the passage of time, under Ibn Rushd, philosophical interpretation again received attention and was developed.